“Une conscience spécifiquement matérialiste”. Rileggendo Phénoménologie et matérialité - Vinti, Carlo (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2020)
This essay intends to be a detailed account/commentary on the Introduction of Le matérialisme rationnel. It is a text that: a) presents, in a nutshell, the entire theoretical horizon of Bachelardian thinking, which revolves around the dualism of reason/imagination; b) contains also, appropriately radicalized, the anti-philosophical polemic performed by Bachelard from an epistemological point of view; c) illustrates, with original features, the notion of matter as it emerges in contemporary science, and the idea of “conscience matérialiste” that accompanies it, suggested by evident phenomenological influences, suggested by clear phenomenological influences. Keywords: Phenomenology, Chemistry, Matter, Subject, Consciousness.